Biodrying and densification of cassava starch industrial waste - Sen, Ranjit; Annachhatre, Ajit P.; Thammarat Koottatep; Salam, Abdul P.; Jabade, Siddharth; National Agricultural Technology Project (NATP); Bangladesh Agricultural Research Council (BARC), Bangladesh (Pathumthani : Asian Institute of Technology, 2015)
Agro-industries like cassava starch industry produce large amount of solid wastes during its processing stage. Presently, these wastes are dumped into roadside and used in land filling. Anaerobic digestion occurs in the waste and methane, one of the major green house gase responsible for global warming, is generated. These wastes can be converted into a value added products like fuel briquette by different physical, chemical and biological treatment process. High moisture present in these wastes is the main obstacle to use them as fuel. Biodrying is an attractive option to dry up these wet wastes. Therefore, an investigation was conducted to study the effect of air flow rate and residence time on biodrying of cassava peel waste. Air flow rates of 0.01 to 0.04 m3kg-1h-1 and residence times of 12 to 20 days were maintained during biodrying. Calorific value of cassava peel increased from its initial value of 4,660 KJ kg-1 to a maximum value of 10,406 KJ kg-1 (wet weight basis) when air flow rate of 0.03 m3kg-1h-1 and residence time of 16 days were maintained during biodrying. Under this operating condition, moisture content of cassava peel reduced from its initial value of 70.40% to a final value of 24.00%. Air flow rate of 0.03 m3kg-1h-1 with 16 day residence time was found optimum for biodrying of cassava peel waste yielding an increase of 123% in calorific value. After biodrying, biodried wastes are converted into fuel briquette through densification process. Biodried cassava peel wastes were dried up to 4%, 8%, 12% and 16% moisture content and were used as raw material for briquette production. Suitable moisture content for briquette production was found 8%. Optimum cassava peel moisture for briquette production was determined by the response function of density of briquette to cassava peel moisture. From regression equation, optimum moisture content for briquette production was found 9.5%. To optimize particle size of cassava peel, briquettes were produced from < 2 mm, 2-5 mm and 5-8 mm sized cassava peel, and was found 2-5 mm particle size most suitable for briquette production. Biodried cassava peel wastes were mixed with three ligno-cellulosic binders namely rice husk, coconut dust and saw dust at the ratio of 100:0, 90:10, 80:20, 70:30 and 60:40. Screw press extruder with heated die was used for densifying cassava peel waste. Both the type and amount of binders significantly influence the physical properties (true density, compressive strength, shattering resistance, resistance to water penetration) and combustion properties (calorific value) of briquettes. Among the three binders, rice husk was found better than coconut dust and saw dust. From economic analysis, it was also found that briquettes produced from cassava peel to rice husk at the ratio of 70:30 yielded the highest benefit cost ratio (BCR) of 1.91 with highest gross margin of 3.94 Baht kg-1 and net margin of 3.81 Baht kg-1. At this ratio, briquettes exhibit highest density of 841 kg m-3, compaction ratio of 5.86, compressive strength of 21.09 kg cm-2, shattering resistance of 97.49%, resistance to water penetration of 94.17% and calorific value of 15,691 KJ kg-1. Briquettes produced from cassava peel with rice husk at the ratio of 70:30 can be store upto 80 days in warehouse in open condition (without any cover). For storing long time in warehouse, briquettes must keep with polythene cover to prevent briquettes from absorbing atmospheric moisture. Biodrying coupled with densification process is profitable to convert the wet agro-industrial waste to produce fuel briquette, a CO2 neutral green energy.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Environmental Engineering and Management, School of Environment, Resources and Development
Thesis (Ph.D.) - Asian Institute of Technology, 2015
Keywords: Agricultural wastes -- Environmental aspects; Cassava industry